Nailfold Dermatoscopic Findings and Its Relationship with Proteinuria - Dilek GİBYELİ GENEK; Ceyda TETİK AYDOĞDU (Namık Kemal Tıp Dergisi, 2022)

(untitled)
Aim:Proteinuria is estimated to be a marker of microvascular damage. The aim of this study was to identify dermatoscopic findings of the nailfold capillary in patients with proteinuria and the relationship of these findings with the level of proteinuria.Materials and Methods:Our study is observational cross-sectional study. Eighty five proteinuric patients whose albumin/creatinine ratio was found to be above 30 mg/gr in the spot urine in routine tests and eighty five non-proteinuric patients participated in this study. Proteinuric patients were separated into three groups (microalbuminuria, macroalbuminuria and overt proteinuria). Nailfold capillaroscopy was examined by a specialist dermatologist with a hand dermatoscope.Results:The presence of at least one capillary dermatoscopic finding was significantly higher in the patient group with proteinuria when compared to the control group (62 vs. 14%, p<0.05). Capillary ectasia and presence of giant capillaries, appearance of subpapillary venous plexus, capillary disorganization and decrease in capillary density were found to be significantly higher in patients with proteinuria compared to the control group (p<0.05). However, there was no significant difference between the levels of proteinuria with nailfold dermatoscopic findings.Conclusion:In our study, the presence of at least one capillary dermatoscopic finding was significantly higher in patients with proteinuria. We reported that dermatoscopic examination of nailfold capillaries in diseases with proteinuria might be an indicator of the microvascular damage. Further investigations with more patients are needed in this area.